2014
DOI: 10.1373/clinchem.2013.215434
|View full text |Cite
|
Sign up to set email alerts
|

Invention and Validation of an Automated Camera System That Uses Optical Character Recognition to Identify Patient Name Mislabeled Samples

Abstract: BACKGROUND Mislabeled samples are a serious problem in most clinical laboratories. Published error rates range from 0.39/1000 to as high as 1.12%. Standardization of bar codes and label formats has not yet achieved the needed improvement. The mislabel rate in our laboratory, although low compared with published rates, prompted us to seek a solution to achieve zero errors. METHODS To reduce or eliminate our mislabeled samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…An electronic ID system is an additional successful measure to minimize specimen ID errors [ 6 , 8 , 20 , 28 33 ]. Reducing patient ID errors in the demanding ED environment is critical and should therefore be the first target for incorporation of an electronic ID system.…”
Section: Discussionmentioning
confidence: 99%
“…An electronic ID system is an additional successful measure to minimize specimen ID errors [ 6 , 8 , 20 , 28 33 ]. Reducing patient ID errors in the demanding ED environment is critical and should therefore be the first target for incorporation of an electronic ID system.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 An automated camera system using optical character recognition was utilized to detect samples with patient name labeling errors. 71 An ML model was applied to identify instances of incorrect blood samples in the complete blood count results. 72 Recently, Yang et al developed a DL-based system for evaluating serum quality by analyzing sample images.…”
Section: And Risk Management Of Clinical Laboratory Testsmentioning
confidence: 99%
“…Studies employing ML models to identify mislabeled samples have shown that even relatively straightforward ML models can outperform humans 69,70 . An automated camera system using optical character recognition was utilized to detect samples with patient name labeling errors 71 . An ML model was applied to identify instances of incorrect blood samples in the complete blood count results 72 .…”
Section: Study Of Ai Application In Qc and Risk Management Of Clinica...mentioning
confidence: 99%
“…Innovative approaches are also emerging for univocal patient identification, such as human hand back skin texture detection (32), probabilistic matching (33) or near field communication (NFC). Interestingly, Hawker et al recently developed and validated an automated device based on four cameras which photographs the outside of a sample tube and then recognizes discrepancies between patient identity in the LIS versus that on the blood tube label by means of optical character recognition (OCR) (34). The system was found to have a high sensitivity for labeling errors (i.e., out of 742,977 total images that were passed, zero were mislabeled by patient name or exhibited patient name spelling discrepancies, yielding to 1.00 sensitivity; 95% CI 0.97–1.00), whereas the specificity was still modest (only 121 true patient mislabels were identified in the 266,853 images classified as fails by the system, yielding to 0.74 specificity; 95% CI 0.73–0.74).…”
Section: What the Future Holdsmentioning
confidence: 99%